Osman Bakar. Tahwid and Science: Islamic Perspectives on Religion and Science (2nd Edition). Kuala Lumpur: Arah Publications, 2008 - Al-Aidrus, Mohamed Ajmal (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The often touted statement of the immense contribution of Islam to world civilization, especially in the area of science and mathematics, is sometimes ignored by many because its an achievement of the too distant past and it too remote to produce any measurable excitement in those who live in the present. In some instances, a constant reminder of an antiquated truth, even a factual one, produces a quaint response in people who do not place too much stock in the past. Familiarity breeds contempt, and repetition indifference. Yet, those who do speak of the glory days of Islam today sometimes cannot themselves enumerate specifically what Muslims had attained in his history and fall back on general statements that sound like fantastic claims from unverifiable sources rather than substantive facts. However, Professor Emeritus Dr. Osman Bakar supplements the veracity of the assertions of Muslims with evidence in his book. Tawhid and Science, and also provides cogent arguments on the motivation that brought success in the past.